Polevaya T. N. Influence of substituions on the evaluative component of meaning when translating mass media texts - Polevaya T. N. (Philological Treatises, 2020)
The article explores the influence of various types of substitutions on the evaluative component of the meaning, basing on the material provided by mass-media. The author analyzes cases of appearance, change and loss of the evaluative component that may occur when translating from Belarusian into English.